Case Report: Therapeutic potential of traditional Korean herbal medicine Jeopgol-tang in bone regeneration: a case series of delayed union over 5 months - Cho, Eunbyul; Lee, Seri; Choi, Youngjin; Yang, Changsop; Woo, Hyeonjun (Frontiers in Endocrinology, 2025)
The delayed union of fractures poses considerable challenges in orthopedic treatment, affecting patients’ quality of life and healthcare outcomes. Although various treatment options are available, their efficacy may be limited in patients with prolonged delayed union. This study investigated the therapeutic potential of Jeopgol-tang (JGT), a traditional herbal decoction, for treating cases of delayed union persisting for more than 5 months. Three patients with different fracture sites (pubic ramus, multiple metatarsals, and femoral neck) who exhibited insufficient healing after conventional treatment were administered JGT (100 mL per pack, twice daily) for 2–6 months depending on individual healing progress and fracture complexity. Radiological assessments demonstrated progressive improvement in all cases. Notably, one patient avoided reoperation after exhibiting initial signs of bone healing within 1 month of treatment, whereas all patients achieved complete union and reported improved mobility and reduced pain. These findings suggest that JGT could be an effective complementary treatment option for delayed union, particularly in cases in which conventional treatments have yielded limited success. Nevertheless, larger prospective clinical trials and mechanistic studies are required to validate these results and to explore the therapeutic mechanisms of JGT.